Assessment of the Socio Economic and Political Implications of ECOWAS Free Movement - & Moses M. Duruji, Agape J. Apwenum, Kester Onor (Covenant University Journal of Politics and International Affairs, 2020)
This paper examines the extent the ECOWAS free movement protocol of persons, goods and services contributes to the economic and political growth of Nigeria which is an active member state. The protocol on free movement is often hijacked by criminals from some member states, neighbors and within to perpetrate trans-border crimes such as smuggling of arms, drugs and other forms of crimes. Political development is the heart beat of other development in any country. This is because power rest in political sphere and it is through power that other development such as economic development rest. The system of government in place, the ideals of the government and the stability of the government determine the profitable, societal plus cultural improvement of the nation. The role plays by civil societies, mass media and some section of activists toward the return to democracy in Nigeria are more appreciated and noticeable than that of ECOWAS. This indicates that there is always romance between ECOWAS and West African dictators especially in Nigeria. This unholy relationship might not be far from the fact that most leaders under ECOWAS are once dictators who benefited from the silence of the community or the leaders are mute considering the benefit their individual states get from dictators in Nigeria. The study primarily adopted the desk research design which involves the use of secondary source of data. The analyses of the data were carried out using content analysis. The study revealed that the performance of ECOWAS were undermined by various factors such as lack of political will, fear and mutual distrust, cultural and colonial differences among others. These factors inhibited the full actualization of the protocol among member states. The study concluded that Nigerian government should evaluate her activities in ECOWAS and should ensure that member states contribute their quota to the community as enshrine in the treaty.Â